Coffin Road - May, Peter, 1951- (New York : Quercus, 2016)
In the Outer Hebrides of Scotland, a man washes up on a deserted beach with no knowledge of who he is or how he got there, while homicide detective George Gunn makes the ocean crossing to a remote lighthouse on a rock in the North Atlantic to investigate a brutal murder.
Keywords: Amnesiacs -- Fiction; Murder -- Investigation; Fiction; Fathers and daughters -- Fiction; Secrecy -- Fiction; Western Isles (Scotland) -- Fiction; Detective and mystery fiction; Thrillers (Fiction)